ANALISIS PERFORMA TURBIN PELTON SUDU SEGITIGA DENGAN VARIASI SUDUT SEMPROT NOSEL - Riani, Novi Indah; Masykur, Masykur; Abidin, Zainal (universitas teuku umar, 2022)
The availability of electrical energy in Indonesia is a very important factor in encouraging development. Increased development, especially in the industrial sector in the form of factories and home industries, continues to grow rapidly. These developments include economic and population growth, so that the need for electrical energy continues to increase. The Pelton turbine is an electrical energy generator that utilizes water as a propeller or bucket on the rotating wheel of the Pelton turbine. So that, it is expected as an alternative to provide electrical energy needs, especially in the industrial sector. This study aims to determine the effect of variations in the angle of the nozzle spray on the triangular blade on the performance of the Pelton turbine. The variations of the nozzle spray angle include 30º, 45º, and 90º. Each nozzle spray angle is varied to the valve opening angle of 60º, 75º, 90º with lamp loads of 0, 5, 10, 15, 20, 25 Watt. Based on the results of this study, it is proven that the nozzle spray angle of 90º has the best results at a valve opening angle of 90º and a lamp load of 15 Watt which produces a generator power of 6.784 Watt with an efficiency of 54.04%. Keywords— Pelton turbine with triangular blade, nozzle spray angle, valve opening angle, generator power, efficiency.